Rice production technical efficiency in a highly urbanised area in Samut Prakan Province, Thailand - Naruebet Meelua; Suneeporn Suwanmaneepong (International Journal of Entrepreneurship and Small Business, 2024)
This study investigates rice farmers' technical efficiency in a highly urbanised area in Samut Prakan Province, Thailand. The study used a two-stage data envelopment analysis (DEA) in measuring farmers' level of technical efficiency (TE), while a Tobit regression was employed to assess the factors affecting TE. The results revealed that rice farmers' TE levels ranged from 0.53-1.00, with an overall mean value of 0.84, indicating a considerable potential in enhancing TE to improve rice production. Moreover, the study found cultivated area, education level, and rice farming experience significantly affected production efficiency; whereas the significant association of the land area to the production efficiency suggests the need for government to be cautious about converting land areas for non-agricultural activities brought by urbanisation growth. Lastly, the study suggests improving TE levels through more substantial policy support and programmes targeting the strengthening of rice farmers' technical knowledge.
Keywords: Agricultural Economics and Practices